Pengaruh Self-Compassion terhadap Psychological Well-Being pada Mahasiswa Etnis Minangkabau di Kota Bandung - Tri Asi Sucikaputri; Endah Nawangsih (UNISBA Press, 2022)
Abstract. Migrating is something that a person does to seek or find a better life from where he came from. Students who migrate aim to get a better education from their place of origin. During the overseas period, students often experience difficulties that can affect their psychological well-being. Self-compassion is said to be a predictor of psychological well-being. This study was conducted to determine how much influence self-compassion has on psychological well-being in Minangkabau ethnic overseas students in Bandung. Self-compassion is measured by the Self-Compassion Scale (Sugiyanto, 2020) and psychological well-being is measured by the Indonesian version of the psychological well-being (Rahmayandi & Ramadanty, 2014). The participants in this study were 350 ethnic Minangkabau immigrant students in the city of Bandung, consisting of 242 women (69%) and 108 men (31%). This research is a quantitative research with causality design and analyzed using simple regression analysis. The main results of this study indicate that self-compassion affects the psychological well-being of Minangkabau ethnic overseas students in Bandung City with a contribution of 39.7%. This study predicts that every increase in self-compassion, it can increase psychological well-being by 89.3%. Abstrak. Merantau merupakan suatu hal yang dilakukan seseorang untuk mencari atau menemukan kehidupan yang lebih baik dari tempat asalnya. Mahasiswa yang merantau bertujuan untuk memperoleh pendidikan yang lebih baik dari tempat asalnya. Selama masa perantauan, mahasiswa kerap kali mengalami kesulitan yang dapat mempengaruihi psychological well-being nya. Self-compassion dikatakan merupakan prediktor bagi psychological well-being. Penelitian ini dilakukan untuk mengetahui seberapa besar pengaruh self-compassion terhadap psychological well-being pada mahasiswa rantau etnis Minangkabau di Kota Bandung. Self compassion diukur dengan alat ukur Skala Welas Diri (Sugiyanto, 2020) dan psychological well-being diukur dengan alat ukur psychological well-being versi Bahasa Indonesia (Rahmayandi & Ramadanty, 2014). Partisipan pada penelitian ini adalah 350 mahasiswa perantau etnis Minangkabau di kota Bandung, yang terdiri dari 242 perenpuan (69%) dan 108 laki-laki (31%). Penelitian ini merupakan penelitian kuantitatif dengan design kausalitas dan dianalisis menggunakan analisis regresi sederhana. Hasil utama dari penelitian ini menunjukkan bahwa self-compassion berpengaruh terhadap psychological well-being pada mahasiswa rantau etnis Minangkabau di Kota Bandung dengan sumbangan sebesar 39.7%. Penelitian ini memprediksi bahwa setiap kenaikan self-compassion, maka dapat meningkatkan psychological well-being sebesar 89,3%.